The Importance of Taxpayer Awareness and Legal Sanctions for All Levels of Indonesian Society - Budiman, Eunike Kathryn; Pangestu, Kartika; Yunita, Theresia; Siswanto, Vivienne Olivia (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
One of the characteristics of a developed country can be seen from the high awareness of its citizens to pay taxes. Taxes are one of the country's largest sources of income, which come from the people and are useful for the welfare of the people's lives. Therefore, awareness to pay taxes is very important. In this case, the state has the authority to collect taxes from its people. Tax revenue received will later be used to increase Indonesia's development starting from the development of infrastructure, education, health and various other sectors that aim for the welfare and prosperity of the Indonesian people. However, judging from the data received and the facts on the ground, unfortunately in Indonesia itself awareness of paying taxes is still very low. Not only that, the state apparatus in charge of taxation still makes a lot of negligence and mistakes. These things hampered the existing taxation system in Indonesia.